Shigellosis non responsive to "sensitive" antibiotics - De Silva, J. R. S.; Sumanasena, S. P.; Wilegoda, M. S. S.; S K Arulmoly2, S. K. (Sri Lanka College of Paediatricians, 2001)
Shigellosis is the commonest cause of blood and mucus diarrhoea among children1. In Sri Lanka Shigella flexneri is the predominant serotype isolated and S. dysenteriae takes the third place1,2. Worldwide there is an evolving antibiotic resistance3. In common practice furazolidone still remains the drug of choice at the first presentation and gentamicin is reserved for severe infections.

Introduction Shigellosis is the commonest cause of blood and mucus diarrhoea among children1 . In Sri Lanka Shigella flexneri is the predominant serotype isolated and S. dysenteriae takes the third place1,2 . Worldwide there is an evolving antibiotic resistance3 . In common practice furazolidone still remains the drug of choice at the first presentation and gentamicin is reserved for severe infections.
Keywords: shigellosis; children